Lung Cancer in Never-Smokers: A Multicenter Case-Control Study in North China - Liang, Di; Wang, Jingxi; Li, Daojuan; Shi, Jin; Jing, Jin; Shan, Baoen; He, Yutong (Frontiers in Oncology, 2019)
This study aimed at estimating the effects of epidemiological risk factors for lung cancer in never-smokers. A multicenter and matched case-control study was conducted in the cities of Shijiazhuang, Xingtai, Qinhuangdao, Baoding, and Chengde in North China. It comprised 1086 cases and 2172 healthy subjects as controls, all of whom had smoked fewer than 100 cigarettes in their lifetimes. Patients were newly diagnosed with lung cancer between January 2015 and December 2017. Each patient was matched to two control participants for sex and age (±5 years). Along with the univariate and multivariate conditional logistic regression model was used to estimate odds ratio (OR) and 95% confidence interval (95% CI). Subsequently, data were stratified by participant sex and different air quality conditions for analysis. Type of job, exposure to environmental tobacco smoke in the workplace or at home, more exposure to cooking oil fumes, depression, poor sleep quality, occupational exposure, cardiovascular diseases, and family history of cancer were revealed as significant risk factors for lung cancer in never-smokers. However, higher educational level, frequent use PM2.5 mask, cooking using clean fuels, and consumption of dietary supplements and tea reduced the risk of lung cancer. Risk factors varied between males and females. In areas with air pollution, the number of risk factors was greater than elsewhere, and their magnitude effects were different. Hence, focus on these risk factors is important for the prevention and control of lung cancer in never-smokers.